Understanding of the halalan tayyiban concept towards purchase intention of halal cosmetics among young urban muslim consumers - Sutono (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)
This study investigates understanding of the halalan tayyiban concept and its influence on purchase intention of halal cosmetics. The data was collected through a self administered questionnaire survey with purposive sampling on a population of 560 Indonesian young urban Muslim consumers. A structural equation modelling technique was used to test the proposed model. Understanding of the halalan tayyiban concept was found to be predictor of attitude towards halal cosmetics.Attitude was found to influence purchase intention of halal cosmetics. This study is one of the first attempts to empirically test the value-attitude-behavior model in the context of halal cosmetics purchasing behavior. The study provides useful information for marketers as well as policy makers.